Dragging into the open: the polythetic nature of areas of endemism. Issue 6 (18th August 2018) - Apodaca, María José; Crisci, Jorge V.
Abstract : Areas of endemism represent territories (no matter the size) of non-random overlap in the geographic distribution of two or more taxa, reflecting a common spatial history of these taxa. The common spatial history is a result of different processes that connect areas of endemism to evolutionary theory. Numerous and diverse definitions of areas of endemism have been proposed. All of them have used as the conceptual foundation of the definition a certain degree of non-random congruence of geographic distribution amongst at least two taxa. 'Certain degree' means that geographic congruence does not demand complete agreement on the boundaries of those taxa's distributions at all possible scales of mapping. The words 'certain degree' mask the polythetic nature of areas of endemism. The polythetic characterization of areas of endemism implies that each locality of the study area has a large number of a set of species. Each species of this set is present in many of those localities and, generally, none of those species is present in every locality of the area. The converse will be a monothetic nature of areas of endemism where a taxon or group of taxa is present in all the localities of the study area. We propose here that the expansion of the definition of areas of endemism, including their polythetic characterization, will improve understanding of large biogeographic areas such as realms, regions, provinces, and districts, and will increase the scientific content (e.g., predictive capability and explanatory power) of areas of endemism.